A Tribute to „Barocco”: The Figurativeness of Maria Morska - Szulc-Woźniak, Agata (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The paper focuses on the figure of Maria Morska, a reciter dubbed “Skamander muse”, who had a versatile and multifaceted impact on the literary circles of her day. I am conducting the quest for the artist (elusive today in the face of scarce biographical sources) through interpreting the poems for which she was a magnet and a centre (i.e. Inwokacja by Antoni Słonimski and Groteska by Jarosław Iwaszkiewicz). The image of Morska emerging from them presents a very original figure: one that was admired and received intensely. The poetic inscriptions of the impression which the Skamander muse made often bring to mind the reception of works of art. Morska refines commonness into a metaphor. Her literary image is a testimony to a moment of delight, dazzle, and – perhaps more importantly – spontaneous, artistic co-participation. She inspires one to look for pseudonyms and roles which would be capable of expressing the impression that accompanied her – one of changeability, glimmer, being different, never being the same.